LAS TIC EN LA ORIENTACIÓN AFECTIVA DE LOS ESTUDIANTES POR LA LICENCIATURA EN EDUCACIÓN MATEMÁTICA-FÍSICA: ICT IN THE AFFECTIVE ORIENTATION OF STUDENTS FOR THE DEGREE IN MATHEMATICS-PHYSICAL EDUCATION - Rodríguez Benítez, Alexeis; Álvarez Cortés, Alexis Benancio; Urquiza Humara, Wilfredo (Opuntia Brava, 2018)
El artículo parte del pobre interés de los estudiantes cubanos por el estudio de la Física como ciencia y hacia la carrera pedagógica de Matemática-Física y argumenta la utilización de las nuevas dotaciones de laboratorios y las tecnologías de la información y las comunicaciones (TIC) para potenciar en los estudiantes la orientación afectiva por la Física, como ciencia y como docencia. Se plasman logros del impacto positivo en docentes y estudiantes de preuniversitario en el interés por la Física que evidencian la factibilidad de la propuesta. ABSTRACT The poor interest of the Cuban students towards the study of Physics as a science and toward Mathematics-Physics pedagogical career motivated the author of this article to use the new laboratories as well as the information and communicationtechnologiesforstrengtheningaffectiveorientationtowardsPhysics as a science and as a subject. An impact was achieved both in teachers and studentstowardstheirmotivationforPhysics.Scientificmethodswereusedtodiagnosethelevel of motivation of the students for the study of this science. The results obtained in the application of the experience during four school courses in this topic evidenced the feasibility of the proposal. This article is part of a doctoral degree is the by its author. KEY WORDS: affective orientation, Physics, experimental activity.